Microstructure-related piezoelectric properties of a ZnO film grown on a Si substrate. Issue 15 (15th November 2016) - Qin, Wei Wei; Li, Yu Tong; Li, Tao; Qiu, Jun Wen; Ma, Xian Jun; Wei, Du; Chen, Xiaoqiang; Hu, Xue Feng; Zhang, Wei
Abstract: We investigated the effect of grain size on the piezoelectric properties of ZnO using films of different grain sizes and a fixed thickness of 800 nm deposited on a Si substrate by pulsed laser ablation in the temperature range of 300–700 °C. All of the deposited films have a crystal structure with a c-axis orientation. The grain size of the grown films, characterized by transmission electron microscopy (TEM), increases with the deposition temperature. In contrast, their piezoelectric efficiency (PE, d33 ), characterized by piezoelectric force microscopy (PFM), was found to initially increase with the deposition temperature up to 500 °C, after which it decreased with further increases in temperature. The maximum PE value is observed for the film deposited at 500 °C with a grain size of approximately 60 nm. The peculiar PE behavior observed was theoretically explained by a competition between the contribution of the c-axis orientation favoring a larger d33 value due to the enhanced static asymmetry and the strong grain size effect that influences the piezoelectric polarization as a result of domain motion.